MAQASID SYARIAH DAN METODE PENETAPAN HUKUM DALAM KONTEKS KEKINIAN (Memahami Korelasi antara Keduanya) - Muhammad Sabir; Abdul Muher (IAIN Ambon, 2021)
Maqasid sharia is a concept that is becoming an interesting conversation among scholars. This concept has been known long before syatibi but this concept is very attached to it because it was introduced the first complete as a method of legal thought by him. Substantially, the maqasid of sharia or the purpose of establishing the law is nothing but benefit. In understanding the maqasid of sharia, there are two methods of legal determination that can be developed, namely the ijtihad tatbiqi and istinbati methods. Both methods have support from the ta'lili reasoning style and the istislahi ta'lili reasoning style with the qiyas and stihsan methods while istislahi reasoning with maslahah mursalah and saddu zara'i. such things all have a relationship with the maqasid of sharia. Apart from that the correlation is that there is a close relationship between the maqasid of sharia and the method of establishing law, the linkages are interconnected so that they cannot be separated. Maqasid shari'ah as a goal and a method as a tool to understand the meaning and purpose of Allah and His Messenger in ordering and prohibiting something.